On viticulture tradition (Some examples from the south of Dalmatia) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
This paper presents data about economic conditions in the valley of the Trebišnjica River and its immediate vicinity in ancient times. Written source materials and archaeological discoveries point to main industrial branches under the Roman power. A significant number of material remnants which are the evidence of economic occupations in the valley of the Trebišnjica River of that period were found. In Marina and in the suburb Bihovi near the town of Trebinje, the facility of economic character was found, namely the remnants of ancient device for obtaining oil and wine. What is also significant is a sign found in the south of the province of Dalmatia, where sign poster’s cognomen denotes his profession — wine-grower. These testimonies have exceptional historical value, as they give a more detailed description of economic circumstances and the tradition of wine production in East Herzegovina region from ancient times onwards.
Keywords: Panik; Marina; valley of the Trebišnjica River; East Herzegovina; South of Dalmatia; tradition; viticulture